Case Report: De novo variant of the NUS1 gene associated with developmental delay and autism spectrum disorders in a Chinese family - Ding, Feng; Pan, Junlin; Ji, Shuhua; Zhang, Yan; Hou, Jinwei; Shi, Na; Liu, Haiping (Frontiers in Pediatrics, 2025)
BackgroundNuclear undecaprenyl pyrophosphate synthase 1 (NUS1) has been implicated in the pathogenesis of neurodevelopmental disorders, including Parkinson's disease, seizures, intellectual disability, dystonia, and congenital disorder of glycosylation. To this day, there have been limited studies and reports on the NUS1 gene.MethodsWe described the case of an 8-year-old Chinese boy exhibiting developmental delay, intellectual disability, and autism spectrum disorder (ASD). To elucidate the genetic etiology, whole-exome sequencing was performed on the proband. A candidate variant was subsequently validated by Sanger sequencing in the proband and his unaffected parents.ResultsWhole-exome sequencing analysis discovered a novel heterozygous variant (c.279del, p.L94Wfs*11) on exon 1 of NUS1 (NM_138459.5), leading to premature termination of protein translation (p.L94Wfs*11). Sanger sequencing failed to identify the candidate variant in his unaffected parents. Following the updated American College of Medical Genetics and Genomics guidelines, the c.279del variant was classified as pathogenic (PVS1+PM6+PM2_Supporting). Based on the clinical phenotype of the proband, he was diagnosed with autosomal dominant intellectual developmental disorder-55 with seizures (MRD55) and ASD.ConclusionsThis study expands the phenotype and mutation spectrum of the NUS1 gene, which contributes to the diagnosis of related disorders. Furthermore, the identification of the genetic basis of the proband and confirmation of the corresponding loci of his family members will facilitate the genetic counseling of the proband's parents regarding reproduction.